2021
DOI: 10.1002/iid3.400
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of canakinumab in mild or severe COVID‐19 pneumonia

Abstract: Background Clinicians all around the world are currently experiencing a pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Several therapeutic strategies have been used until now but, to date, there is no specific therapy to treat SARS‐CoV‐2 infection. In this study, we used canakinumab, a human monoclonal antibody targeting interleukin‐1 beta to improve respiratory function and laboratory parameters compared with standard therapy (hydroxycloroquine plus lopinavir/rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
0
36
0
1
Order By: Relevance
“…The results showed that canakinumab treatment significantly increased the PaO 2 /FiO 2 ratio and reduced inflammatory indices. 263 These two studies suggest that canakinumab treatment may have therapeutic potentials in non-ICU patients with mild or severe COVID-19. Several other reports have also evaluated the administration of canakinumab in COVID-19, 264 266 and six clinical trials are currently registered in ClinicalTrials.gov (NCT04348448, NCT04476706, NCT04362813, NCT04365153, NCT04510493, NCT04278404).…”
Section: Blockade Of Cytokinesmentioning
confidence: 98%
“…The results showed that canakinumab treatment significantly increased the PaO 2 /FiO 2 ratio and reduced inflammatory indices. 263 These two studies suggest that canakinumab treatment may have therapeutic potentials in non-ICU patients with mild or severe COVID-19. Several other reports have also evaluated the administration of canakinumab in COVID-19, 264 266 and six clinical trials are currently registered in ClinicalTrials.gov (NCT04348448, NCT04476706, NCT04362813, NCT04365153, NCT04510493, NCT04278404).…”
Section: Blockade Of Cytokinesmentioning
confidence: 98%
“…Arrhythmic Ca 2+ release was observed especially after long-term exposure to COVID19 serum. In the present study, the IL-1β blocker Canakinumab was used to potentially mitigate these in-vitro effects, as Canakinumab has been shown to improve outcomes in mild or severe COVID19 pneumonia in early clinical trials with limited numbers of patients [ 33 ]. However, chronic co-incubation with Canakinumab had no beneficial effect on cellular Ca 2+ signaling during excitation-contraction coupling or on electrical dysfunction in our iPS-CM model.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, therapy with a human monoclonal antibody targeting IL-1β (canakinumab) in Covid-19 has been reported to cause a reduction in inflammation, and an improved respiratory function with reduced oxygen need, implicating a potential role of IL-1β in severe Covid-19. 9 However, a randomized trial utilizing another IL-1β neutralizing drug (Anakinra) did not show any benefit. 10 Thus, the pathogenic role of IL-1β for severe Covid-19 as well as therapeutic neutralization as potential treatment needs to be further determined.…”
Section: Clonal Hematopoiesis In Patients With Covid-19 Is Stable and Not Linked To An Aggravated Clinical Coursementioning
confidence: 99%